"Keep a low profile": pesticide residue, additives, and freon use in Australian tobacco manufacturing. (26th November 2003) - Chapman, S
Abstract : Objectives: To review the Australian tobacco industry's knowledge of pesticide residue on Australian tobacco and its policies and practices on resisting calls by tobacco control advocates that consumers should be informed about pesticide residue as well as additives. Methods: Review of previously internal industry documents relevant to pesticides and additives in Australian tobacco located from the Master Settlement Agreement websites. Results: Between 1972 and 1994 Philip Morris Australia was aware that its leaf samples were often contaminated with pesticide residue, sometimes including organochlorine levels described by PM's European laboratories as being "extremely high". Consumers were not advised of the contamination nor products withdrawn. From 1981, the industry also resisted calls to declare fully the extent of use and long term safety data on all additives used in their products. They developed standard public responses that were evasive and misleading and, in 2000, implemented voluntary additive disclosure which allowed the companies to continue to avoid disclosure of any ingredient they deemed to be a trade secret. There was extensive use of ozone depleting freon in Australian tobacco manufacturing. Again, the industry kept this information away from consumers. Conclusions: Australian smokers are unable to make informed decisions about smoking because pesticide and additive disclosure remains voluntary. The Australian government should regulate tobacco to require full disclosure including information on the likely health consequences of inhaling pesticide and additive pyrolysis products.